Exposure to Cadmium and Lead in Cigarette Smokers Who Switched to Electronic Cigarettes. Issue 9 (9th August 2018) - Prokopowicz, Adam; Sobczak, Andrzej; Szuła-Chraplewska, Magdalena; Ochota, Patryk; Kośmider, Leon
Abstract: Introduction: Electronic cigarettes (ECs) seem to be a less harmful alternative for conventional cigarettes. This study aimed to assess whether the generated aerosols from ECs contain lower amount of cadmium (Cd) and lead (Pb) than cigarette smoke and to detect any changes in exposure to Cd and Pb among cigarette smokers who switched completely or partially to EC. Methods: EC aerosols and cigarette smoke were generated, and the determination of Cd and Pb in trapped samples and e-liquids was performed by the electrothermal atomic absorption spectrometry method. A cross-sectional, group-based survey was carried out using 156 volunteers classified into groups of nonsmokers, EC-only users, dual EC users-cigarette smokers, and cigarette-only smokers. Using electrothermal atomic absorption spectrometry, blood Cd and Pb levels were measured, and the results were compared by analysis of covariance. Results: Transfer of Cd and Pb to EC aerosol was found to be minimal, although the metals were present in the remaining e-liquid from tanks used for vapor generation. The geometric mean blood Cd concentration adjusted for age and sex was 0.44 (95% confidence interval = 0.37 to 0.52) µg/L in the EC-only users, which was significantly lower than those in the smokers of 1.44 (1.16 to 1.78) and dual users of 1.38 (1.11 to 1.72). The blood Pb geometric mean differed significantly only between nonsmokers of 11.9 (10.6 to 13.3) and smokers of 15.9 (13.6 to 18.6). Conclusion: The study revealed that smokers who completely switched to ECs and quit smoking conventional cigarettes may significantly reduce their exposure to Cd and probably Pb. Implications: Switching to EC use is associated with a rapid and substantial decrease in the exposure to carcinogenic Cd. Exposure to Pb is probably also decreased but may be overshadowed by other factors. The study provides empirical data based not only on the analysis of generated aerosol but also on biological indicators of recent exposure—that is, the concentrations of Cd and Pb in blood, indicating EC as a potential harm-reduction device, especially regarding Cd exposure. However, in this case, dual EC use-cigarette smoking provides doubtful benefits.